2016
DOI: 10.1186/s12889-016-3812-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a randomized controlled intervention trial on return to work and health care utilization after long-term sickness absence

Abstract: BackgroundThe aim of the RCT study was to investigate if the effect of a multidisciplinary intervention on return to work (RTW) and health care utilization differed by participants’ self-reported health status at baseline, defined by a) level of somatic symptoms, b) health anxiety and c) self-reported general health.MethodsA total of 443 individuals were randomized to the intervention (n = 301) or the control group (n = 142) and responded to a questionnaire measuring health status at baseline. Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…A further limitation might be that the analyses and results are based on data collected in 2004-2007. However, despite changes in business cycles, and financial initiatives from the Swedish government to improve rehabilitation and sick leave management promoting return to work, the results from recent rehabilitation and vocational intervention studies show results similar to the present one [16,24,25,27,28].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A further limitation might be that the analyses and results are based on data collected in 2004-2007. However, despite changes in business cycles, and financial initiatives from the Swedish government to improve rehabilitation and sick leave management promoting return to work, the results from recent rehabilitation and vocational intervention studies show results similar to the present one [16,24,25,27,28].…”
Section: Discussionsupporting
confidence: 65%
“…However, several previous studies, with interventions similar to the present one, have evaluated the effects of rehabilitation on sick leave conclusion in sickness-certified patients. We found six randomised controlled trials (RCT) [16,[23][24][25][26][27], one study with a matched two-cohort design [21], and one review [28]. Johansson et al [16] concluded that the intervention prolonged sickness absence spells, as we did.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Anema et al [26] found a positive effect of workplace intervention in subjects with low back pain but no effect of graded activity. The Danish return-to-work programme [27] found that a multidisciplinary intervention did not facilitate return to work or decrease health care utilisation as compared to ordinary case management in patients with somatic symptoms, anxiety or low self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…The review revealed that the time to RTW, cumulative sickness absence, the proportion of RTW at short-term follow-up or ever did not differ from care as usual. In a more recent randomized controlled study a multidisciplinary intervention did not facilitate RTW or decrease health care utilization compared to ordinary case management and could even reduce the chance of RTW in some patients [27].…”
Section: Strengths and Limitationsmentioning
confidence: 93%